Radiation-induced intestinal injury: from molecular mechanisms to clinical translation - Wu, Wenjue; Cai, Yubo; Yang, Zhi; Chen, Mengshuang; Hu, JianYang; Qu, Kunlong; Yang, Jian (Oncology Reviews, 2025)
Radiation-induced intestinal injury (RIII) poses a significant clinical challenge for patients undergoing pelvic or abdominal radiotherapy, characterized by dual features of acute symptoms (diarrhea, abdominal pain, rectal bleeding) and chronic complications (stricture, fistula, chronic pain), profoundly impacting quality of life. Despite high clinical prevalence, the molecular and cellular mechanisms underlying RIII remain poorly defined, hindering therapeutic development. Current diagnostic modalities (imaging, endoscopy) lack sensitivity and specificity for early detection or real-time monitoring. While biomarkers offer promise for non-invasive assessment and prognosis, existing candidates face limitations in reproducibility and clinical applicability. Therapeutic options, ranging from pharmaceuticals to surgery, show variable efficacy, underscoring the need for optimized strategies. This review systematically explores RIII pathogenesis, emphasizing radiation-induced immune dysregulation, epigenetic alterations, and gut microbiota dysbiosis. We discuss potential biomarkers, such as miRNA, fatty acid binding proteins (FABPs), etc. We categorize therapies into radioprotectors (pre-radiation use) and radiomitigators (post-radiation intervention), highlighting natural plant-derived compounds and traditional Chinese medicine (TCM) for their multi-target effects, alongside emerging approaches like stem cell and microbiota transplantation, with discussions on their therapeutic potential and clinical challenges. Crucially, we exclusively summarize recent clinical translation advances to accelerate drug development. Through critical evaluation of evidence, we propose future directions to refine risk stratification, enable timely intervention, and improve long-term outcomes for irradiated patients. This integrative analysis aims to bridge translational gaps and prioritize research avenues for RIII management.